Islamic microfinance: an ethical alternative to poverty alleviation - Abdul Rahman, Abdul Rahim (Emerald Group Publishing, 2010)
Purpose – The purpose of this paper is to assess the potential of Islamic financing schemes for microfinancing purposes. Design/methodology/approach – The paper contends that Islamic finance has an important role to contribute for furthering socio-economic development of the poor and small (micro) entrepreneurs without charging interest (read: riba’). Findings – Islamic finance offers various ethical schemes and instruments that can be advanced and adapted for the purpose of microfinance. Comparatively, qardhul hasan, murabahah, and ijarah schemes are relatively easy to manage and will ensure the capital needs (qardhul hasan), equipments(murabahah) and leased equipments (ijarah) for potential micro-entrepreneurs and the poor. Participatory schemes such as mudarabah and musharakah, on the other hand, have great potentials for microfinance purposes as these schemes can satisfy the risk sharing needs of the microentrepreneurs. Research limitations/implications – The paper is only conceptual and does not aim to empirically examine the issues or theories. However, the paper will definitely be useful to develop hypotheses for future research, especially in this relatively new area of Islamic microfinance. Practical implications – The Islamic concepts of microfinance will be of interest especially to many microfinance institutions. The paper will also be a good introduction to practitioners in the microfinance sector to understand the relevance and limitations of Islamic financing schemes. Originality/value – Islamic financing schemes are argued as having moral and ethical attributes that can effectively motivate micro-entrepreneurs to thrive. These schemes, however, require specialized skills in managing risks inherent in the structure of the contracts. In theory, different schemes can be used for different purposes depending on the risk profile of the micro-entrepreneurs.